STUDY OF DYNAMIC POVERTY IN EAST JAVA : IS HUMAN CAPITAL THE MOST APPROPRIATE WAY IN REDUCING POVERTY? - Wahyu Wisnu Wardana (East Java Economic Journal, 2017)
Dynamic poverty analysis distinguishes two kind of poverty: chronic and transient poverty. Chronic poverty is long term poverty while transient poverty is short term poverty. Theoretically, these two kind of poverty need different policy. Chronic poverty needs human capital development whereas transient poverty needs social safety net. This study aims to estimate chronic and transient poverty in East Java and to analyze its determinants. This research used Component Approach to estimate chronic and transient poverty. Tobit regression was employed to analyze its determinants. This study utilized Survei Sosial Ekonomi Nasional (Social Economic National Survey of Indonesia) year 2008 and year 2010. The result of this study indicates that poverty in East Java is largely comprised of chronic poverty. Chronic component of poverty is 76 percent and transient component of poverty is 24 percent. The high chronic component of poverty is found in regency of, Malang, Kediri, Sumenep, and Pasuruan. The regression result indicates that chronic and transient poverty are influenced by education of household head, gender of household head, access to credit and health insurance ownership. JEL Classification: C01, I32, I38, J24,